1998
DOI: 10.1046/j.1523-1755.1998.00004.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of acute renal failure on mortality in end-stage liver disease with or without transplantation

Abstract: The Nijmegen Biomedical Study is a population-based cross-sectional study conducted in the eastern part of the Netherlands. As part of the overall study, we provide reference values of estimated glomerular filtration rate (GFR) for this Caucasian population without expressed risk. Age-stratified, randomly selected inhabitants received a postal questionnaire on lifestyle and medical history. In a large subset of the responders, serum creatinine was measured. The GFR was then measured using the abbreviated Modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
158
3
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(177 citation statements)
references
References 15 publications
13
158
3
3
Order By: Relevance
“…As a result of a higher incidence of complications, patients with acute renal failure stayed significantly longer in the ICU and in hospital with a marked impact on the cost of the procedure [10,19]. The significantly lower 6-month survival rate in patients with acute renal failure (79% vs 98%) agrees with that reported elsewhere in the literature (50-62% vs 87-100%) [2,4,[6][7][8][9]. Six month after transplantation, 46% of our patients with acute renal failure still had impaired renal function, which is a risk factor for the development of chronic renal failure [13,16].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…As a result of a higher incidence of complications, patients with acute renal failure stayed significantly longer in the ICU and in hospital with a marked impact on the cost of the procedure [10,19]. The significantly lower 6-month survival rate in patients with acute renal failure (79% vs 98%) agrees with that reported elsewhere in the literature (50-62% vs 87-100%) [2,4,[6][7][8][9]. Six month after transplantation, 46% of our patients with acute renal failure still had impaired renal function, which is a risk factor for the development of chronic renal failure [13,16].…”
Section: Discussionsupporting
confidence: 81%
“…Acute renal failure can occur early in the postoperative course and seems to be related to pre-operative conditions and to the operative procedure. Impaired renal function and especially the need for post-transplant renal replacement therapy is associated with prolonged hospitalisation, increased mortality [2,[7][8][9], and significant financial cost [10].These observations prompted this prospective observational study, with the aim of developing a prediction model to identify patients at risk for acute renal failure requiring renal replacement therapy directly at the end of the transplantation procedure. Therefore we investigated only pre-and intra-operative risk factors for the development of acute renal failure after orthotopic liver transplantation, postoperative risk factors such as nephrotoxic drugs or postoperative complications having been extensively studied in the past.…”
mentioning
confidence: 99%
“…Severe IR injury results in a systemic inflammatory response and end organ damage. AKI is a particular problem post AKI and documented rates in the literature range from 14% to 94% [29][30][31][32][33][34] . A recent audit of incidence of AKI at the Royal Free Hospital found that AKI occurs in around 50% of patients undergoing liver transplantation.…”
mentioning
confidence: 99%
“…[7][8][9][10] Preoperative serum creatinine levels have been shown to be an important predictor of postoperative sepsis, 11,12 number of days spent in the intensive care unit, 3,13 need for preoperative and postoperative dialysis, 2,13 overall cost of liver transplantation, 13,14 and short-term graft and patient survival rates. 1,7,8,11,12,15 In one study, 2-year patient and graft survival rates were found to be similar in 31 patients with HRS and 263 without HRS. 16 However, in a follow-up study, the same investigators found significantly lower graft and patient survival rates at 5 years in patients with HRS but not in non-HRS-induced renal failure.…”
mentioning
confidence: 99%